2002
DOI: 10.1152/japplphysiol.01240.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic and resistance exercise on central hemodynamic responses in severe chronic heart failure

Abstract: Exercise is now considered an important component of management in chronic heart failure (CHF), but little is known about central hemodynamic changes that occur during different exercise modalities in these patients. Seventeen patients (ejection fraction 25 +/- 2%) undertook brachial artery and right heart catheterization and oxygen consumption assessment at rest, during submaximal and peak cycling (Cyc), and during submaximal upper and lower limb resistance exercise. Cardiac output (CO) increased relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 24 publications
6
27
1
2
Order By: Relevance
“…Periphery changes enable the muscle to uptake more oxygen from the blood contributing to an increased arterialvenous oxygen difference rather than increase in stroke volume and cardiac output [50]. It was demonstrated that stroke volume of severe chronic heart failure patients did not change or even decrease during exercise (both aerobic and resistance) [51]. Moreover, the maximal heart rate in the present chronic heart failure patients did not change after training.…”
Section: Discussionmentioning
confidence: 64%
“…Periphery changes enable the muscle to uptake more oxygen from the blood contributing to an increased arterialvenous oxygen difference rather than increase in stroke volume and cardiac output [50]. It was demonstrated that stroke volume of severe chronic heart failure patients did not change or even decrease during exercise (both aerobic and resistance) [51]. Moreover, the maximal heart rate in the present chronic heart failure patients did not change after training.…”
Section: Discussionmentioning
confidence: 64%
“…This may be because of the heightened systolic and diastolic pressure loading that occurs with strength training (36 -38). Moreover, the strength-training-mediated increase in LV wall stress, coupled with the impaired contractile and preload reserve, could explain why LV stroke volume and EF do not increase when HF patients perform this type of exercise (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies have suggested that during resistance exercise LV function of cardiac patients remains stable or is enhanced [33,36]. Cheetham et al [37] examined the effect of both isometric (40% of maximal voluntary contraction) and isotonic (submaximal and maximal cycling) exercises on cardiac output, SV and heart rate of patients with CHF including a sub-group of patients on beta-blocker medication. They reported that during isometric exercise and submaximal cycling, cardiac output did not change significantly in both modes of exercises.…”
Section: Discussionmentioning
confidence: 99%